2019
DOI: 10.1002/aps3.1209
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of ESTSSR markers for Vitex negundo var. heterophylla (Lamiaceae)

Abstract: Premise of the Study Vitex negundo var. heterophylla (Lamiaceae) is a dominant shrub in the warm temperate zone of northern China. Expressed sequence tag–simple sequence repeat (EST‐SSR) markers were developed to investigate its genetic diversity and structure.Methods and ResultsWe detected 12,075 SSRs in V. negundo var. heterophylla using transcriptome sequencing. Primer pairs for 100 SSR loci were designed and amplified in three populations of V. negundo var. heterophylla. Sixty loci were amplified, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…And the results showed that there were significant relationships between epigenetics and genetic variation, epigenetics, and phenotypic variation. Liu et al (2019) have developed 14 pairs of expressed sequence tags and simple repeat sequence (EST-SSR) marker primers for this species, which provided useful resources for the study of reproduction and genetic ecology of V. negundo var. heterophylla.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the results showed that there were significant relationships between epigenetics and genetic variation, epigenetics, and phenotypic variation. Liu et al (2019) have developed 14 pairs of expressed sequence tags and simple repeat sequence (EST-SSR) marker primers for this species, which provided useful resources for the study of reproduction and genetic ecology of V. negundo var. heterophylla.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. ( 2019 ) have developed 14 pairs of expressed sequence tags and simple repeat sequence (EST‐SSR) marker primers for this species, which provided useful resources for the study of reproduction and genetic ecology of V. negundo var. heterophylla .…”
Section: Introductionmentioning
confidence: 99%
“…Through various extraction techniques as well as using different solvents it was estimated that the luteolin content in leaves can be attained to its maximum by reflux technique and using methanol as solvent. From the leaves genomic DNA was extracted using the cetyltrimethylammonium bromide method and 12,075 simple sequence repeat markers were detected 87 . The flavonoid extract of flower buds showed the presence of phenols, naphthalene, 2,3-dihydrobenzofuran, 5-hydroxy-3,6,7,3' ,4'-pentamethoxy flavones, phenol-2,4-Bis flavones through GCMS analysis 88 .…”
Section: Clinical Studiesmentioning
confidence: 99%